The Effect of Using Animation Media on Students' Physics Learning Outcomes in Linear Motion Material - Ihfa Indira Nurnaifah; Mariani Akhfar; Sukmawati Said (Universitas Lambung Mangkurat, 2024)
This quasi-experimental research was conducted with the aim of 1) comparing the learning outcomes of students taught conventionally and those taught using animation media and 2) calculating the value of the influence of using animation media on student learning outcomes. The experimental research design used in this research is in the form of a nonequivalent control group design with a test as the research instrument, carried out at the research's beginning (pretest) and end (posttest). The sample classes in this study are two classes that were taken using the cluster random sampling method. The results obtained are: 1) The average physics learning outcomes of students in the experimental class are higher than the average learning outcomes in the control class, and 2) There is a significant difference in learning outcome scores between classes that have been taught using animation media compared to conventional classes so that animation media has an influence on students' physics learning outcomes in Pinrang. The research becomes a reference for physics teachers in Pinrang who use animation media in the learning process.